Locawe – Developing Platform for Mobile Ubiquitous Services - Luimula, Mika; Markkula, Jouni; Kuutti, Kari (International Journal of Industrial Engineering and Management, 2010)
Development of new advanced mobile ubiquitous multimedia services presents number of challenges which needs to be addressed in service platform design. We have been developing our Locawe platform for this goal in several research projects using systematic develop-evaluate design cycle as a research approach. During the development we have build an adaptive architecture, which we have learned to be a key requirement for a usable and sustainable service platform. The result of a number of field studies, including various field experiments and industrial pilots, have verified our solutions and proven our approach to be successful. Our Locawe platform has shown to be applicable and useful for developing different types of mobile ubiquitous services that utilise the latest technological possibilities. Article history: Received (01.12.2010); Revised (23.12.2010); Accepted (24.12.2010)